Exploring Online Asynchronous Counseling With Tobacco Treatment Specialists in the QUIT-PRIMO and National Dental PBRN HI-QUIT Studies: Who Uses It and What Do They Say?. Issue 5 (June 2018) - Williams, Jessica H.; DeLaughter, Kathryn; Volkman, Julie E.; Sadasivam, Rajani S.; Ray, Midge N.; Gilbert, Gregg H.; Houston, Thomas K.
Purpose: To describe the content of messages sent by smokers through asynchronous counseling within a Web-based smoking cessation intervention. Design: Qualitative. Setting: National community-based setting of patients who had been engaged by the medical or dental practices at which they attended or via Google advertisements. Participants: Adults older than 19 years who were current smokers and interested in quitting. Participants throughout the United States referred to a Web-based cessation intervention by their medical or dental provider or by clicking on a Google advertisement. Methods: We conducted a qualitative review of 742 asynchronous counseling messages sent by 270 Web site users. Messages were reviewed, analyzed, and organized into qualitative themes by the investigative team. Results: The asynchronous counseling feature of the intervention was used most frequently by smokers who were white (87%), female (67%), aged 45 to 54 (32%), and who had at least some college-level education (70%). Qualitative analysis yielded 7 basic themes—Talk about the Process of Quitting, Barriers to Quitting, Reasons to Quit, Quit History, Support and Strategies for Quitting, Quitting with Medication, and Quit Progress. The most common theme was Support and Strategies for Quitting with 255 references among all messages. Conclusion: We found rich communication across the spectrum of the quit process, from persons preparing to quit to those who had successfully quit. Asynchronous smoking cessation counseling provides a promising means of social support for smokers during the quit process.